Pengaruh Kinerja Keuangan, Modal Intelektual, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Sektor Perbankan Yang Terdaftar Di Bei - Seuk , Ordiana; Mulida , Alfiatual; Kusumawardhani, Ratih (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of financial performance, intellectual capital, and company size on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach and secondary data from 20 banking companies between 2020–2024, the study employed multiple linear regression analysis. Results show financial performance has a significant positive effect on firm value, while intellectual capital and company size do not. The findings suggest that profitability is a key factor in enhancing firm value. These results provide insight for investors and companies in evaluating growth strategies and investment decisions.